Sporadic Creutzfeldt–Jakob disease diagnostic accuracy is improved by a new CSF ELISA 14-3-3γ assay. (13th May 2016) - Leitão, M.J.; Baldeiras, I.; Almeida, M.R.; Ribeiro, M.H.; Santos, A.C.; Ribeiro, M.; Tomás, J.; Rocha, S.; Santana, I.; Oliveira, C.R.
Highlights: We quantified CSF 14-3-3γ in 72 sCJD and 73 Non-CJD patients, by a new ELISA assay. WB and ELISA 14-3-3γ results matched in 81% of all cases. WB inconclusive cases were further discriminated by ELISA 14-3-3γ assay. ELISA 14-3-3γ is the best single predictive marker for sCJD early diagnosis. PRNP genotype did not influence ELISA 14-3-3γ protein levels. Abstract: Protein 14-3-3 is a reliable marker of rapid neuronal damage, specifically increased in cerebrospinal fluid (CSF) of sporadic Creutzfeldt–Jakob disease (sCJD) patients. Its detection is usually performed by Western Blot (WB), prone to methodological issues. Our aim was to evaluate the diagnostic performance of a recently developed quantitative enzyme-linked immunosorbent (ELISA) assay for 14-3-3γ, in comparison with WB and other neurodegeneration markers. CSF samples from 145 patients with suspicion of prion disease, later classified as definite sCJD ( n = 72) or Non-prion diseases (Non-CJD; n = 73) comprised our population. 14-3-3 protein was determined by WB and ELISA. Total Tau (t-Tau) and phosphorylated Tau (p-Tau) were also evaluated. Apolipoprotein E gene ( ApoE ) and prionic protein gene ( PRNP ) genotyping was assessed. ELISA 14-3-3γ levels were significantly increased in sCJD compared to Non-CJD patients ( p < 0.001), showing very good accuracy (AUC = 0.982; sensitivity = 97%; specificity = 94%), and matching WB results in 81% of all cases. It strongly correlated with t-Tau and p-Tau ( p < 0.0001), showing slightly higher specificity (14-3-3 WB – 63%; Tau – 90%; p-Tau/t-Tau ratio – 88%). From WB inconclusive results ( n = 44), ELISA 14-3-3γ correctly classified 41 patients. Additionally, logistic regression analysis selected ELISA 14-3-3γ as the best single predictive marker for sCJD (overall accuracy = 93%). ApoE and PRNP genotypes did not influence ELISA 14-3-3γ levels. Despite specificity for 14-3-3γ isoform, ELISA results not only match WB evaluation but also help discrimination of inconclusive results. Our results therefore reinforce this assay as a single screening test, allowing higher sample throughput and unequivocal results.